La « jeunesse » comme répertoire critique - Jeanne Lamaison-Boltanski (Ateliers d'Anthropologie)
This article analyses the construction and usage of the “youth” category by groups that subscribe to Rastafarianism and hip-hop culture in Burkina Faso. This category, associated with modernity in Africa, was mobilised by groups as proof of their belonging to a “global” identity, and also as a reminder of the political heritage of Thomas Sankara and his revolutionary youth. Asserting rap and Rasta cultures in Burkina Faso thereby contributes to the definition of a new African subject, and to the distancing of links based on primogeniture; it favours new affiliations with other groups, stemming from other political principles, based on Pan-Africanism (or blackness), Sankarism, or globalised representations of “youth”. For Rastas and rappers in Burkina Faso, the “youth” category therefore becomes a major operator in the development of their capacity for local political and social criticism, which is inseparable from criticism of what they call korocracy, that is to say the power of firstborns.